Corrigendum for article: Root canal treatment from patients’ perspective: Knowledge, awareness, and expectations - Editoral (Vojnosanitetski Pregled)
In the original article titled "Root canal treatment from patients’ perspective: knowledge, awareness, and expectations" by Muhammad Qasim*, Omair Anjum†, Gotam Das‡, Fariha Naz*, Saima Razaq Khan§, Abdul Razzaq Ahmed‡, Saurabh Chaturvedi‡, published in the April 2022 print issue of the Vojnosanitetski pregled (Vojnosanit Pregl 2022; 79(4): 325-329); https://doi.org/10.2298/VSP200825112Q), there are errors in affiliations. Instead of the existing affiliations: King Khalid University, College of Dentistry, *Department of Restorative Dental Sciences, ‡Department of Prosthodontics, Abha, Saudi Arabia; Lahore Medical and Operative Dentistry, †Department of Science of Dental Materials, §Department of Operative Dentistry, Lahore, Pakistan, there should be: King Khalid University, College of Dentistry, *Department of Restorative Dental Sciences (Operative Dentistry), ‡Department of Prosthodontics, Abha, Saudi Arabia; Lahore Medical and Dental College, †Department of Science of Dental Materials, §Department of Operative Dentistry, Lahore, Pakistan. Link to the corrected article 10.2298/VSP200825112Q